4(c-6)=(c+2)

Simple and best practice solution for 4(c-6)=(c+2) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 4(c-6)=(c+2) equation:


Simplifying
4(c + -6) = (c + 2)

Reorder the terms:
4(-6 + c) = (c + 2)
(-6 * 4 + c * 4) = (c + 2)
(-24 + 4c) = (c + 2)

Reorder the terms:
-24 + 4c = (2 + c)

Remove parenthesis around (2 + c)
-24 + 4c = 2 + c

Solving
-24 + 4c = 2 + c

Solving for variable 'c'.

Move all terms containing c to the left, all other terms to the right.

Add '-1c' to each side of the equation.
-24 + 4c + -1c = 2 + c + -1c

Combine like terms: 4c + -1c = 3c
-24 + 3c = 2 + c + -1c

Combine like terms: c + -1c = 0
-24 + 3c = 2 + 0
-24 + 3c = 2

Add '24' to each side of the equation.
-24 + 24 + 3c = 2 + 24

Combine like terms: -24 + 24 = 0
0 + 3c = 2 + 24
3c = 2 + 24

Combine like terms: 2 + 24 = 26
3c = 26

Divide each side by '3'.
c = 8.666666667

Simplifying
c = 8.666666667

See similar equations:

| 5h-14=16+4h | | 50+3y=-7y | | 2x+6-7x=21 | | x*x-4x-32=0 | | 17x+3=139 | | 22(2-d)+9=198 | | -2y=3x+10 | | 33x+2880= | | 5+3(s-3t)=0 | | 6p-4=12p+8 | | Df+10=3ford | | 2(n+2)=-11 | | 3(x-5)-8=1-(1x-4) | | -12=6p | | 6p=12p+12 | | 2(2x+3)=-4+2(2x+5) | | 8+5(x+3)+7x= | | log(2x+3)=3 | | r=780d+-13dt | | 8(m-9)=24 | | 3x+6x^2-5x-x^2= | | Sin^2(x)+3sinx-4=0 | | 3g=57 | | -12-w=45 | | 100x-x=12 | | -v+118=182 | | 0.4x+3.9=-5.78 | | (3x+6)(3x+7)=0 | | 5g-6-5-5g= | | 0.75n=46.50 | | -x-4+9=6x-4 | | -x+222=75 |

Equations solver categories